Site‐specific and endothelial‐mediated dysfunction of the alveolar‐capillary barrier in response to lipopolysaccharides. Issue 2 (5th December 2017) - Janga, Harshavardhan; Cassidy, Liam; Wang, Fanlu; Spengler, Dietmar; Oestern‐Fitschen, Stefanie; Krause, Martin F.; Seekamp, Andreas; Tholey, Andreas; Fuchs, Sabine
Abstract: Infectious agents such as lipopolysaccharides (LPS) challenge the functional properties of the alveolar‐capillary barrier (ACB) in the lung. In this study, we analyse the site‐specific effects of LPS on the ACB and reveal the effects on the individual cell types and the ACB as a functional unit. Monocultures of H441 epithelial cells and co‐cultures of H441 with endothelial cells cultured on Transwells ® were treated with LPS from the apical or basolateral compartment. Barrier properties were analysed by the transepithelial electrical resistance (TEER), by transport assays, and immunostaining and assessment of tight junctional molecules at protein level. Furthermore, pro‐inflammatory cytokines and immune‐modulatory molecules were evaluated by ELISA and semiquantitative real‐time PCR. Liquid chromatography–mass spectrometry‐based proteomics (LS‐MS) was used to identify proteins and effector molecules secreted by endothelial cells in response to LPS. In co‐cultures treated with LPS from the basolateral compartment, we noticed a significant reduction of TEER, increased permeability and induction of pro‐inflammatory cytokines. Conversely, apical treatment did not affect the barrier. No changes were noticed in H441 monoculture upon LPS treatment. However, LPS resulted in an increased expression of pro‐inflammatory cytokines such as IL‐6 in OEC and in turn induced the reduction of TEER and an increase in SP‐A expression in H441 monoculture, and H441/OEC co‐cultures after LPS treatment from basolateral compartment. LS‐MS‐based proteomics revealed factors associated with LPS‐mediated lung injury such as ICAM‐1, VCAM‐1, Angiopoietin 2, complement factors and cathepsin S, emphasizing the role of epithelial–endothelial crosstalk in the ACB in ALI/ARDS.